THE INFLUENCE OF COORDINATIVE CAPACITIES DEVELOPMENT OVER THE GAME QUALITATIVE INDICES OF THE 16-17 YEARS OLD RUGBY PLAYERS - Bragarenco Nicolae; Tabîrța Vasile; Gorașcenco Alexandr (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
This article reflects the experimental argumentation of coordinative capacities development influence over sports mastery level and competitive activity of junior rugby players in the training process. According to assumption regarding the use of ways of development of coordinative capacities of junior rugby players within sport training, that will influence direct over qualitative indices game, it was developed the experimental program which was proposed to the experimental group, which includes methods and specific ways to the targeted development of the coordinative capacities, while the bystander group followed the traditional training. The both of the groups were checked through the video method, official matches from internal championship at the beginning and ending of pedagogical experiment, the dates being processed mathematical -statistically and presented in tabular and graphical form. Analyzing final results, we can assert that the submitted hypothesis at the beginning of researches was justified, which allowed the ascending of sports mastery, the improvement of the game qualitative indices in the competitive activity through the implementation of ways of directed development of the coordinative capacities in the training process of junior rugby players of 16-17 years old.